Pistachio frost damage in Iran and new methods of frost protection - Hokmabadi H. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
With climate change we can expect increased damage to orchards, such as increased winter and spring frost, summer droughts, storms, and increased damages from fungi and insect attacks. Particularly in winter we can expect a temperature increase, and the trees natural annual rhythm will gradually fall further out of step with the climate of the region. Higher winter temperatures will reduce the hardiness and lead to an earlier growth start. The tree mechanisms for avoiding such damage do not appear to be able to prevent this. First, trees can have problems with de-hardening in mild weather periods and frost damage in the subsequent cold periods. Particularly unfortunate are fluctuations between above- and below-freezing temperatures (thaw-freeze cycles) for trees that are adapted to a continental climate. In the south and west parts of Iran, there has been a wide-spread and increasing problem with such damage over several years. In average 50 percent of pistachio was damaged by spring frost in the last five years. New methods of frost protection were applied in the last few years for controlling frost damage in pistachio orchards in Kerman province. One of these methods was the design and manufacturing of a SIS (selective inverted sink) system and testing it in pistachio orchards. Results showed that this system can protect orchards and can increase temperature by 2°C. The other system was the fogger machine. This system was also designed and manufactured and tested in pistachio orchards. The results of this system showed 11.5 pour cent increase in relative humidity and 1.9°C increase in temperature of orchards. The new methods of frost control in orchards in Iran are explained in this paper and the importance of frost damage in horticultural plants in Iran is discussed.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)